Burnout syndrome, sociodemographic, occupational, and job satisfaction variables in a hospital nursing staff - Barbosa, Bruna Silveira Toledo (2020)
This is a quantitative study carried out from 2015 to 2016, to evaluate the prevalence of Burnout syndrome and its associations with the sociodemographic factors, occupational characteristics, and job satisfaction of nursing workers. A semi-structured questionnaire was used for sociodemographic and occupational assessment. The Maslach Burnout Inventory was used as an index for Burnout syndrome, and the Occupational Stress Indicator for job satisfaction. The mean age of workers was 33.73±8.33 years. Most were female (82.2%) and had moderate risk prevalence (52.3%) for Burnout Syndrome. The higher the job satisfaction, the lower the risk for Burnout Syndrome. It is important that these professionals have adequate working conditions to reduce the risk of a disease that jeopardizes the quality of life and the assistance provided.